Effect of the silicon carbide nanoparticles introduction on biological properties of porous polymer coatings. Issue 18 (5th March 2015) - Mzyk, A.; Major, R.; Lackner, J. M.; Bruckert, F.; Wilczek, P.; Major, B.
<x xml:space="preserve">Abstract</x> The multilayer polyelectrolyte films (PEMs) seem to be a promising material to reconstruct the structure and behavior of the extracellular matrix.